Consecuencias de la expansión europea para los pueblos de ultramar - Rabeder, Gernot; Pohar, Vida; Pacher, Martina (Book collections on Project MUSE., 2014)
During 1999 and 2001 re-excavations in Križna jama were carried out, which brought crucial results concerning the taxonomical and stratigraphical position of the fossil taphocoenosis, especially of cave bears, and on their ethology. Moreover new data on the hydrological structure of the cave as well as on its sedimentology were published. A substantial part of this volume is dedicated to the extant fauna of this cave, which is extraordinary rich in species.